Psychological Landscape of Children With Cleft Palate: A Comprehensive Review - Christabella, Rininta; Evillia, Wati (Jurnal Plastik Rekonstruksi, 2024)
Cleft lip and/or palate (CL/P) is a common congenital craniofacial abnormality with significant psychosocial implications. This review synthesizes recent research on the psychological landscape of children and adolescents with CL/P, emphasizing the impact on emotional well-being, social functioning, and quality of life. Psychological distress, including anxiety and lower self-esteem, is prevalent among individuals with CL/P, persisting into adulthood and influencing various aspects of mental health. While some studies suggest resilience or underreporting of psychological difficulties, others highlight enduring challenges in appearance satisfaction and emotional well-being. Factors such as familial support and satisfaction with appearance play crucial roles in positive adjustment. Social functioning and peer acceptance present significant challenges, with many children experiencing isolation and stigma. However, some demonstrate adaptive social behaviours, suggesting protective factors. Quality of life is adversely affected, emphasizing the need for holistic interventions addressing physical and psychosocial aspects. While treatments positively impact perceived quality of life, specific cleft types and comorbidities like obstructive sleep apnea further influence outcomes. Overall, understanding the multifaceted challenges of CL/P is essential for implementing targeted interventions and improving overall well-being. Further research is needed to assess the long-term effectiveness of interventions and identify novel approaches for enhancing mental health in this population.